BnaA03.ANS Identified by Metabolomics and RNA-seq Partly Played Irreplaceable Role in Pigmentation of Red Rapeseed (Brassica napus) Petal - Hao, Pengfei; Liu, Han; Lin, Baogang; Ren, Yun; Huang, Lan; Jiang, Lixi; Hua, Shuijin (Frontiers in Plant Science, 2022)
Colorful flowers of rapeseed (Brassica napus L.) have been a hotspot for researchers, but the underlying mechanisms of pigment formation still need to be clarified. In this study, two stages of unopened rapeseed petals with red, white and yellow colors were selected to identify the metabolites and genes involved in red pigment formation. Metabolomic analysis showed that flavonoids as the most class among common differentially accumulated metabolites involved in red pigment formation had high accumulation in red rapeseed than in white and yellow. RNA-seq analysis showed that among common differentially expressed genes involved in red pigment formation, anthocyanin (belonging to flavonoids) biosynthesis pathway was largely regulated with ANS, DFR and UF3GT higher-expressed in red rapeseed petals.RNA interference of BnaA03.ANS in red rapeseed transferred petal colors from raspberry red to beige red and zinc yellow under different interference levels, with pelargonidin, cyanidin, lutein, neoxanthin, β-carotene and lycopene contents significantly inhibited. However, overexpression of BnaA03.ANS in yellow rapeseed did not change yellow petal color. This study confirmed the important function of flavonoids, especially anthocyanins on red pigment formation, and for the first time, identified the irreplaceable role of BnaA03.ANS on red flowered rapeseed.